2020
DOI: 10.1158/1078-0432.ccr-19-1425
|View full text |Cite
|
Sign up to set email alerts
|

Potent Cell-Cycle Inhibition and Upregulation of Immune Response with Abemaciclib and Anastrozole in neoMONARCH, Phase II Neoadjuvant Study in HR+/HER2− Breast Cancer

Abstract: Purpose: neoMONARCH assessed the biological effects of abemaciclib in combination with anastrozole in the neoadjuvant setting. Patients and Methods: Postmenopausal women with stage I-IIIB HR þ /HER2 À breast cancer were randomized to a 2-week lead-in of abemaciclib, anastrozole, or abemaciclib plus anastrozole followed by 14 weeks of the combination. The primary objective evaluated change in Ki67 from baseline to 2 weeks of treatment. Additional objectives included clinical, radiologic, and pathologic response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 38 publications
(53 reference statements)
8
130
0
3
Order By: Relevance
“…The results showed that the abemaciclib arm had better median PFS than the placebo arm (28.18 versus 14.76 months) [149], which also led to the FDA approving abemaciclib (Verzenio) in combination with aromatase therapy in HR+/HER2− M/ABC patients as first-line therapy in February 2018. In addition, other ongoing studies with abemaciclib in BC were carried out, such as the neoMONARCH (NCT02441946) phase II clinical trial to compare the biological effects of abemaciclib combination with anastrozole to those of abemaciclib monotherapy and anastrozole monotherapy for two weeks, as well as to evaluate the activity and safety of abemaciclib with anastrozole in a subsequent 14 weeks with HR+/HER2− ABC [150]. The monarchE study (NCT03155997) assessed the safety and efficacy of abemaciclib combined with standard endocrine therapy versus endocrine therapy alone in high-risk, node-positive, early-stage BC [131].…”
Section: The Clinical Success Of Cdk4/6-selective Inhibitors In Bcmentioning
confidence: 99%
“…The results showed that the abemaciclib arm had better median PFS than the placebo arm (28.18 versus 14.76 months) [149], which also led to the FDA approving abemaciclib (Verzenio) in combination with aromatase therapy in HR+/HER2− M/ABC patients as first-line therapy in February 2018. In addition, other ongoing studies with abemaciclib in BC were carried out, such as the neoMONARCH (NCT02441946) phase II clinical trial to compare the biological effects of abemaciclib combination with anastrozole to those of abemaciclib monotherapy and anastrozole monotherapy for two weeks, as well as to evaluate the activity and safety of abemaciclib with anastrozole in a subsequent 14 weeks with HR+/HER2− ABC [150]. The monarchE study (NCT03155997) assessed the safety and efficacy of abemaciclib combined with standard endocrine therapy versus endocrine therapy alone in high-risk, node-positive, early-stage BC [131].…”
Section: The Clinical Success Of Cdk4/6-selective Inhibitors In Bcmentioning
confidence: 99%
“…Abemaciclib was investigated as neoadjuvant therapy in combination with anastrozole in the phase II neoMONARCH trial, showing that abemaciclib, alone or in combination with anastrozole, led to potent cell-cycle arrest after 2 weeks of treatment compared with anastrozole alone, 58%-68% of patients treated in the abemaciclib arms versus 14% of patients treated with anastrozole alone achieved CCCA (p < 0.001) and a pCR rate of 4% with abemaciclib plus anastrozole. The study also assessed gene expression changes related to cell proliferation and immune response, showing that the combination therapy inhibited cell-cycle processes and estrogen signaling and resulted in increased cytokine signaling and adaptive immune response indicative of enhanced antigen presentation and activated T-cell phenotypes [107]. Recently, Eli Lilly Company announced that phase III MONARCH-E trial (NCT03155997) met its primary endpoint of invasive disease-free survival (iDFS), showing that the combination of abemaciclib and standard ET led to a significant decrease in the risk of BC recurrence or death compared with adjuvant ET alone in patients with high-risk node-positive HR-positive, HER2-negative early BC.…”
Section: Neoadjuvant/adjuvant Therapymentioning
confidence: 99%
“…In particular, a neoadjuvant study can investigate how certain resistance mechanisms are overcome by CDK4/6 inhibitors. Data regarding abemaciclib were already available from the Neo-Monarch study that showed that abemaciclib leads to marked cell cycle arrest in the neoadjuvant setting 54 . In this connection, the FELINE study, which investigated neoadjuvant use of ribociclib, has now been reported 55 .…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…Insbesondere kann in einer neoadjuvanten Studie untersucht werden, wie durch CDK4/6-Inhibitoren gewisse Resistenzmechanismen überwunden werden. Zu Abemaciclib lagen aus der Neo-Monarch-Studie hierzu bereits Daten vor, die gezeigt haben, dass Abemaciclib in der Neoadjuvanz zu einem deutlichen Zellzyklusarrest führt 54 . In diesem Zusammenhang wurde nun die FELINE-Studie berichtet, die Ribociclib in der Neoadjuvanz untersucht hat 55 .…”
Section: Neoadjuvante Cdk4/6-inhibitortherapieunclassified